Analysis of Anta Group's Profitability under the Background of Digital Transformation - Xuan Wang (Journal of Frontier in Economic and Management Research, 2025)
Against the dual backdrop of the rapid development of the digital economy and the continuous promotion of national sports industry policies, the digital transformation of traditional manufacturing has become a key path to enhance the core competitiveness of enterprises. This paper takes Anta Group, a leading enterprise in China's sports goods industry, as the research object. Based on its financial data from 2020 to 2024, the DuPont analysis method is employed to systematically analyze the impact mechanism and path of digital transformation on the profitability of the enterprise. The research shows that digital transformation significantly improves the net profit margin of the enterprise by promoting changes in the DTC (Direct-to-Consumer) model, optimizing supply chain management, and implementing refined operations, making it the core driving force for the growth of return on net assets. Although in the early stages of transformation, due to the increase in direct sales channel construction and digital infrastructure investment, the total asset turnover rate experienced some pressure in the short term, this strategic resource investment laid a solid foundation for long-term operational efficiency improvement and profit quality optimization. This paper further proposes targeted suggestions from three dimensions: deepening digital operations, enhancing asset utilization efficiency, and exploring new profit growth points, providing theoretical references and practical insights for promoting high-quality sustainable development in China's traditional manufacturing industry.